Sterols and Triterpene Diols in Virgin Olive Oil: A Comprehensive Review on Their Properties and Significance, with a Special Emphasis on the Influence of Variety and Ripening Degree - Marina Lukić (MDPI AG, 2021)
Olive oil is considered one of the most valuable vegetable oils and is highly appreciated by consumers for its specific and distinguishable taste and aroma, as well as its nutritional value. Sterols and triterpene diols are important carriers of bioactive properties of olive oil and are responsible for some of the beneficial effects of its consumption on human health, such as lowering serum LDL-cholesterol levels and significantly reducing the risk of cardiovascular diseases. The concentration of total sterols and the proportions of particular sterols and triterpene diols are among the parameters used to verify and prove the authenticity of olive oil in accordance with the EU and other countries’ regulations. Finally, their composition has been shown to have high discrimination potential for ensuring traceability with respect to variety, geographical origin, harvest date, and other factors. For these reasons, the research on sterols and triterpene diols in olive oil is an ever-growing field of scientific interest with great practical importance. This review focuses on all the important aspects of sterols and triterpene diols in olive oil, from their chemical structure, biosynthesis, occurrence and role in plants, health benefits, and their use in official controls of olive oil purity and authenticity, to a conclusive survey on the recent findings about the effects of different factors of influence on their content and composition, with a detailed comparative analysis of studies that investigated the effects of the two most important factors, variety and ripening degree.